Islam Nusantara: A Semantic and Symbolic Analysis - Woodward, Mark (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2017)
This paper presents a semantic and symbolic analysis of the concept and presentation of the concept of Islam Nusantara and the ways in which it evokes meaning and emotion to counter trans-national violent extremist movements including al-Qaeda and ISIS, based on Salafi-Wahhabi ideologies. It is based on a frame based content analysis of religious and political themes ofIslam Nusantra. I focus primarily on two films produced by Nahdlatul Ulama (NU) to promote this concept: the near feature length (83 minutes)The Blessing of Islam Nusantara (Oceans of Revelation: Islam as a Blessing for All Creation) and the much shorter (8 minutes) Launching the Film The Blessing Islam Nusantara. The first draws on elements of Sufism, Javanese and to a lesser extent other Indonesian cultures to construct a vision of Islam directly countering that of both violent and non-violent Salafi-Wahhabi extremists. The second promotes the film and Ansorâs (the NU youth organization) potential for combatting violent extremism. Theoretically, I rely on insights by Goffmanâs observations concerning the ways in which semantic frames, and more specifically reframing, can alter dominance hierarchies in discourse systems and Sperberâs demonstration that symbolization is a cognitive process that evokes as well as communicates meaning and emotion.